What Makes Employees’ Work So Stressful? Effects of Vertical Leadership and Horizontal Management on Employees’ Stress - Wang, Wei; Sakata, Kiroko; Komiya, Asuka; Li, Yongxin (Frontiers in Psychology, 2020)
Work stress is a significant problem all over the world. In the present study, from the perspective of the combination of vertical and horizontal management, we investigated the relationships of managerial ethical leadership, mutual monitoring, and mutual support among employees’ work stress levels. A total of 307 white collar employees in Japan were asked to complete an online questionnaire on three separate occasions. The results showed that both ethical leadership and mutual support were negatively related to stress. In addition, mutual support mediated the relationship between ethical leadership and work stress. Further, mutual monitoring moderated the relationship between ethical leadership and work stress: when mutual monitoring was high, stress did not decline with more ethical leadership. These results may suggest that ethical leadership can reduce work stress both directly and through mutual support, indirectly. Additionally, the direct effect may be constrained under high-monitoring situations. Practical implications and needed future research are also discussed.